Zasada trwałości przekazania gospodarstwa rolnego następcy de lege lata i de lege ferenda - Lichorowicz, Aleksander (Wydział Prawa i Administracji UAM, 1985)
The author points out a marked divergence between the doctrine and partly also the judicature, and legal regulations. The former jointly indicate the necessity of securing the permanence and irreversibility of the transfer of a farm to a successor, while the latter neither formulate such a principle, nor contain any guarantees of realising it in legal transactions. Having, as a consequence of the above, posed the question whether, in view of the binding legislation, one may speak at all of the existence of a principle of Permanence of the farmis transefr in our law, the author attempts to determine what are the guarantees of permanence in four, (according to him, in practice most significant and at the same time most doubtful) situations: 1) when the transferring farmer has not been qualified for retirement pension, 2) when the successor does not undertake, or relinquishes productive activities on the farm, 3) the transfer of a farm burdened with life annuity, 4) the reservation, in the transfer contract, of the right to renounce the contract. Critically appraising present legislation in this respect, the author postulates a clearer formulation, on the part of the legislator, of the principle of permanence of the transfer, and, simultaneously, proposes motions de lege ferenda as to specific future guarantees of the principle.
The Principle of the Permanent Transfer of a Farm de lege lata and de lege ferenda